Sleep Disturbances in Children Affected by Autism Spectrum Disorder - Galli, Jessica; Loi, Erika; Visconti, Lucrezia Maria; Mattei, Paola; Eusebi, Anna; Calza, Stefano; Fazzi, Elisa; , ASD Collaborative Group; Bonini, Luisa; Merlini, Angela; Pansera, Laura; Malerba, Laura; et al. (Frontiers in Psychiatry, 2022)
Background: Sleep disturbances are common in children affected by Autism Spectrum Disorder (ASD). The aim of our study was to describe sleep characteristics and disturbances in children with ASD, to evaluate possible related factors, and to assess parental stress. Methods: 100 children with a diagnosis of ASD (mean age: 66.7 months, SD: 27.4, range: 24.7 – 152.1 months, n =79 males) were included in the study. We collected data on sociodemographic, clinical, genetic and instrumental variables as well as comorbid conditions. Parents filled out the Questionnaire on sleep behavior in the first years of life, the BEARS questionnaire, and the Parenting Stress Index Short Form. From the analysis on sleep characteristics, we excluded 25 children treated with melatonin. Results: 57 (57%) out of 100 children met the criteria for insomnia. Sleep disorders were associated with developmental or cognitive delay, emotional and behavioral problems (such as anxiety problems and aggressive behaviors) and absence of strategies for inducing sleep after nocturnal awakenings. From parents’ reports, sleep disorders had diurnal repercussions on their offspring; however, we found no statistical correlation between disturbances and family stress. However, no statistical correlation was found between sleep disturbances and the family stress. Also, no significant correlation was found between sleep disturbances and epilepsy. Finally, a statistical correlation was found between the regular intake of melatonin and the resolution of insomnia.) Conclusions: multifactorial variables may be associated to insomnia that could have an impact on the children’ behavior. Clinicians need to be aware of the value of screening for sleep disturbance in children with ASD to integrate sleep interventions in the treatment plan.